Erratum: Graphene oxide/metal nanocrystal multilaminates as the atomic limit for safe and selective hydrogen storage - Eun Seon Cho (Nature Portfolio, 2016)
Nature Communications 7:10804 Article number 10804 (2016); Published 23 February 2016; Updated 18 March 2016 The financial support for this Article was not fully acknowledged. The Acknowledgements should have included the following: The authors gratefully acknowledge research support from the U.S. Department of Energy, Office of Energy Efficiency and Renewable Energy, Fuel Cell Technologies Office, under Contract No.